Postural strain of spinner and casting workers of a small-scale aluminium utensil making factory - Chatterjee, Tapomoy; Mazumder, Sahana; Gangopadhyay, Somnath; Ghorai, Tamal; Samanta, Amalendu (International Journal Of Community Medicine And Public Health, 2023)
Background: Small scale establishments often neglect the worker safety and comfort which impacts both productivity and workers’ safety. Various studies have been conducted in such small-scale establishments but not much has been done on aluminium utensil manufacturing factories. Spinning and casting are two important processes for manufacturing of aluminium utensils. But not much has been studied to assess the hazards of the involved workers. The present study is an attempt to explore this previously unnoticed area. Methods: The study was conducted in different small scale aluminium utensil factories in West Bengal. Sixteen spinners and seventeen casting workers were evaluated for this study. The analysis of posture was done by rapid upper limb assessment (RULA), rapid entire body assessment (REBA) and Ovako working posture analysis system (OWAS). The body parts discomfort was assessed by using Cornell musculoskeletal discomfort questionnaire and Nordic questionnaire was also used to assess the pain they experience. Results: All the casting workers are experiencing postural load beyond the recommended limit whereas in case of spinner, five workers experienced less postural load due to favorable work conditions. Casting workers mainly suffered from low back, neck, right shoulder pain whereas spinners suffered from wrist and finger pain followed by lower extremity pain. Conclusions: Both group of workers are experiencing postural load and discomfort. In case of casting workers, the prevalence was high and immediate interventions are needed. The discomfort is particularly high during the end of shifts.